Influence of electric fields on dielectric properties of GPI ferroelectric - Zachek, I.R.; Levitskii, R.R.; Vdovych, A.S.; Stasyuk, I.V. (Condensed Matter Physics, 2017)
Using modified microscopic model of GPI by taking into account the piezoelectric coupling with strains εi in the frames of two-particle cluster approximation, the components of polarization vector and static dielectric permittivity tensor of the crystal at applying the external transverse electric fields E₁ and E₃ are calculated. An analysis of the influence of these fields on thermodynamic characteristics of GPI is carried out. A satisfactory quantitative description of the available experimental data for these characteristics has been obtained at a proper choice of the model parameters